Stock Prices Predictability at Long-horizons: Two Tales from the Time-Frequency Domain - Nikolaos Mitianoudis; Theologos Dergiades (Credit and Capital Markets – Kredit und Kapital, 2017)
Accepting non-linearities as an endemic feature of financial data, this paper re-examines Cochrane"s "new fact in finance" hypothesis (Cochrane, Economic Perspectives-FRB of Chicago 23, 36–58, 1999). By implementing two methods, frequently encountered in digital signal processing analysis, (Undecimated Wavelet Transform and Empirical Mode Decomposition both methods extract components in the time-frequency domain), we decompose the real stock prices and the real dividends, for the US economy, into signals that correspond to distinctive frequency bands. Armed with the decomposed signals and acting within a non-linear framework, the predictability of stock prices through the use of dividends is assessed at alternative horizons. It is shown that the "new fact in finance" hypothesis is a valid proposition, provided that dividends contribute significantly to predicting stock prices at horizons spanning beyond 32 months. The identified predictability is entirely non-linear in nature. – – Prognostizierbarkeit von Aktienkursen in der langen Frist: Zwei Ansatzpunkte auf der Zeit-/Frequenzebene Dieser Artikel überprüft erneut die "new fact in finance" Hypothese von Cochrane. Die Verfasser akzeptieren dabei die Nichtlinearität von Finanzdaten als endemische Fakten. Unter Anwendung von zwei Methoden, die in digitalen Signalverarbeitungsverfahren häufig zum Einsatz kommen – die stationäre Wavelet-Transformation und die empirische Modenzerlegung teilen die Verfasser die realen Aktienkurse und die realen Dividenden der US amerikanischen Volkswirtschaft in Signale bestimmter Frequenzbänder auf. Unter Einbeziehung der generierten Signale und des Verhaltens in einem nicht-linearen Umfeld, wird die Vorhersagbarkeit von Aktienkursen mit der Hilfe von Dividenden über verschiedene Zeitfenster überprüft. Die "new fact in finance" Hypothese kann bestätigt werden. Dies gilt allerdings nur unter der Voraussetzung, dass Dividenden einen signifikanten Beitrag für die Aktienkursvorhersage für Zeitfenster über 32 Monate leisten. Die im Beitrag identifizierte Prognostizierbarkeit ist jedoch ausschließlich nichtlinearer Natur.
Keywords: G10; C14; C22; C29; 330; Stock prices and dividends; Time-frequency decomposition